2022
DOI: 10.1002/hbm.26156
|View full text |Cite
|
Sign up to set email alerts
|

Fading of brain network fingerprint in Parkinson's disease predicts motor clinical impairment

Abstract: The clinical connectome fingerprint (CCF) was recently introduced as a way to assess brain dynamics. It is an approach able to recognize individuals, based on the brain network. It showed its applicability providing network features used to predict the cognitive decline in preclinical Alzheimer's disease. In this article, we explore the performance of CCF in 47 Parkinson's disease (PD) patients and 47 healthy controls, under the hypothesis that patients would show reduced identifiability as compared to control… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 63 publications
3
10
0
Order By: Relevance
“…This greater, moment-to-moment variability of brain activity was expected from previous observations of pronounced sequent variability of fMRI connectomes in individuals with or at risk of mental health disorders 27 , such as schizophrenia 28 , and in the brain-network fingerprints of patients with PD 31 . Our data extend these observations to spectral derivatives of electrophysiological brain activity.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…This greater, moment-to-moment variability of brain activity was expected from previous observations of pronounced sequent variability of fMRI connectomes in individuals with or at risk of mental health disorders 27 , such as schizophrenia 28 , and in the brain-network fingerprints of patients with PD 31 . Our data extend these observations to spectral derivatives of electrophysiological brain activity.…”
Section: Discussionsupporting
confidence: 68%
“…Our study demonstrates the application and relevance of brain fingerprinting to Parkinson's disease (PD) research. We derived brain-fingerprints from task-free MEG recordings and first replicated the prior observation that the brain-fingerprints of patients with PD present increased variability over short periods of time compared to healthy controls 30,31 . We identified that this effect is due in large part to the enhanced temporal variability of the arrhythmic component of the neurophysiological brain activity of PD patients, making them less distinguishable from one another.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations